1996
DOI: 10.1172/jci118564
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF-alpha gene expression by vitamin A in airway epithelium.

Abstract: The autocrine/paracrine growth mechanism has been implicated in the regulation of bronchial epithelial cell proliferation. By inhibiting the expression of the transforming growth factor-␣ (TGF- ␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Previous studies indicated that treatment with ATRA reduced the levels of TGF-␣ and EGFR mRNA in human SCC cell lines by inhibiting the transcription of these two genes (42), and the RXR-selective retinoid LGD1069 also inhibited both TGF-␣ and EGFR expression in human SCC cell lines (43). Furthermore, in bronchial epithelial cells retinol inhibited TGF-␣ promoter activity in the presence of RAR␤ (44). Our results with ACR are also consistent with evidence that this compound decreases TGF-␣ expression in human hepatoma cells (8).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies indicated that treatment with ATRA reduced the levels of TGF-␣ and EGFR mRNA in human SCC cell lines by inhibiting the transcription of these two genes (42), and the RXR-selective retinoid LGD1069 also inhibited both TGF-␣ and EGFR expression in human SCC cell lines (43). Furthermore, in bronchial epithelial cells retinol inhibited TGF-␣ promoter activity in the presence of RAR␤ (44). Our results with ACR are also consistent with evidence that this compound decreases TGF-␣ expression in human hepatoma cells (8).…”
Section: Discussionsupporting
confidence: 90%
“…First, Shao and colleagues used a much lower concentration of retinoic acid in their culture media ‫ف(‬ 3 ϫ 10 Ϫ10 M versus 5 ϫ 10 Ϫ8 M in our cultures). This is likely relevant because TGF-␣ gene expression is induced by these low concentrations of retinoic acid (70,71). We used the concentration that Koo and colleagues (71) found to be necessary to maintain mucous cell differentiation in NHBE cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The data were analysed with the chi-squared test, Fisher's exact probability test, or one-way analysis of variance with Dunn's multiple comparison (Miller et al, 1966). The data are shown as means ± s.e.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-α has the ability to induce malignant transformation in some epithelial cells (McGeady et al, 1989;Shankar et al, 1989). Miller et al (1996) found that vitamin A suppresses the proliferation of tracheobronchial epithelial cells in culture by inhibiting expression of the TGF-α gene product. They also noted that similar inhibition of the TGF-α mRNA level by retinol was observed in airway explant cultures and in a cell line immortalized from normal human bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 99%